Elementary School-Aged Children's and Parents' Report of Health-Related Quality of Life and Relationships with Lifestyle Measures: A Cross-Sectional Study - Alanne Soili; Koivuniemi Ella; Löyttyniemi Eliisa; Laitinen Kirsi (Switzerland, 2025)
Supporting a child's health-promoting lifestyle is an investment in their future health and health-related quality of life (HRQoL). Particularly children with overweight and obesity may be at an increased risk of a poor HRQoL. Currently, a comprehensive evaluation of lifestyle factors and age in relation to HRQoL in healthy children and, further, separate child and parental proxy-reports of HRQoL are lacking. The aims of this cross-sectional study in Finland are to compare healthy elementary school-aged children's and parents' reports of the child's HRQoL, and to view them in relation to lifestyle markers. The HRQoL was measured with Pediatric Quality of Life InventoryTM 4.0, and the following lifestyle markers: leisure-time physical activity as MET, diet quality via a validated index (ES-CIDQ), sleeping time and screen time by questionnaires. Furthermore, age and BMI were recorded. Data were obtained from 270 primary school-aged children (6-13 years). Female gender, the child's older age (8-13 years), high physical activity level and less screen time were strong predictors of a higher HRQoL in both the child's and parental proxy-reports. Means to promote healthy lifestyles should be particularly targeted to young children, especially boys, and new ways to promote physical activity and other forms of free-time activities should be sought.